Distributed Computing in Sensor Systems First IEEE International Conference, DCOSS 2005, Marina del Rey, CA, USA, June 30-July 1, 2005, Proceedings - Prasanna, Viktor K.; Iyengar, Sitharama; Spirakis, Paul; Welsh, Matt (Computer Communication Networks and Telecommunications,, 2005)
The book constitutes the refereed proceedings of the First International Conference on Distributed Computing in Sensor Systems, DCOSS 2005, held in Marina del Rey, California, USA in June/July 2005. The 26 revised full papers presented were carefully reviewed and selected from 85 submissions; also included are the abstracts of 3 invited talks, 2 short papers, 9 invited poster abstracts, and 10 contributed abstracts.The papers address all current aspects of distributed computing issues in large-scale networked sensor systems, including systematic design techniques and tools, algorithms, and applications.